Economic origins of cultural norms: The case of animal husbandry and bastardy - Christoph Eder; Martin Halla (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
This paper explores the historical origins of the cultural norm regarding illegitimacy (formerly known as bastardy). We test the hypothesis that traditional agricultural production structures influenced the historical illegitimacy ratio, and have had a lasting effect until today. Based on data from the Austro-Hungarian Empire and modern Austria, we show that regions that focused on animal husbandry (as compared to crop farming) had significantly higher illegitimacy ratios in the past, and female descendants of these societies are still more likely to approve illegitimacy and give birth outside of marriage today. To establish causality, we exploit, within an IV approach, variation in the local agricultural suitability, which determined the historical dominance of animal husbandry. Since differences in the agricultural production structure are completely obsolete in today's economy, we suggest interpreting the persistence in revealed and stated preferences as a cultural norm. Complementary evidence from an 'epidemiological approach' suggests that this norm is passed down through generations, and the family is the most important transmission channel. Our findings point to a more general phenomenon that cultural norms can be shaped by economic conditions, and may persist, even if economic conditions become irrelevant.
Keywords: Z1; A13; J12; J13; J43; N33; 330; Cultural norms; persistence; animal husbandry; illegitimacy